Efficient shoot regeneration of medicinal plant Haplophyllum tuberculatum by direct and indirect organogenesis and genetic fidelity assessment using Inter Simple Sequence Repeats markers - Alsafran, Mohammed; Wickramanayake, Kokila; Usman, Kamal; Ahmed, Talaat (Frontiers in Plant Science, 2022)
In vitro plant cell and tissue cultures are potent tools to propagating germplasm resources in conserving and managing plant genetic resources. A reliable micropropagation protocol was developed for efficient callus proliferation and direct and indirect shoot regeneration of Meseika (Haplophyllum tuberculatum). With the applied sterilization procedure, immature, unopened H. tuberculatum seed pods can be identified as a potent explant with high viability and low contamination percentage. Multiple shoots were regenerated from leaf and stem explants through direct organogenesis on Murashige and Skoog’s (MS) + 3% sucrose medium amended with BAP. Indirect regeneration of several shoots was achieved on 1/2 MS + 1% sucrose media amended with 2 and 4 mg/L BAP. An efficient callus proliferation from both explants can be achieved by supplementing the MS media with NAA and BAP. All the cultures were incubated in a controlled growth chamber under 5/19 h light/dark photoperiod, temperature (25 ± 2 °C), and 60% relative humidity (RH).10 ISSR (inter simple sequence repeat) markers were screened to test the genetic fidelity of regenerated H. tuberculatum shoots. Callus development was observed after 15 days and shoot regeneration was occurred after 30 days after callus initiation. 10 ISSR primers produced a total of 39 clear, distinct amplicons. 75%, 60%, 40%, and 16% polymorphism percentages were recorded by the ISSR primer 11, 7, 5, and 4, respectively. The developed micropropagation protocol is appropriate for rapid in-vitro multiplication of H. tuberculatum shoots and callus.